Sustained PKCβII activity confers oncogenic properties in a phospholipase D‐ and mTOR‐dependent manner. Issue 1 (11th October 2013) - El Osta, Mohamad; Liu, Mengling; Adada, Mohamad; Senkal, Can E.; Idkowiak‐Baldys, Jolanta; Obeid, Lina M.; Clarke, Christopher J.; Hannun, Yusuf A.
Abstract : Protein kinase C (PKC) is a family of serine/threonine kinases implicated in a variety of physiological processes. We have shown previously that sustained activation of the classical PKCα and PKCβII induces their phospholipase D (PLD)‐dependent internalization and translocation to a subset of the recycling endosomes defined by the presence of PKC and PLD (the pericentrion), which results in significant differences in phosphorylation of PKC substrates. Here, we have investigated the biological consequences of sustained PKC activity and the involvement of PLD in this process. We find that sustained activation of PKC results in activation of the mammalian target of rapamycin (mTOR)/S6 kinase pathway in a PLD‐ and endocytosis‐dependent manner, with both pharmacologic inhibitors and siRNA implicating the PLD2 isoform. Notably, dysregulated overexpression of PKCβII in A549 lung cancer cells was necessary for the enhanced proliferation and migration of these cancer cells. Inhibition of PKCβII with enzastaurin reduced A549 cell proliferation by >60% (48 h) and migration by >50%. These biological effects also required both PLD activity and mTOR function, with both the PLD inhibitor FIPI and rapamycin reducing cell growth by >50%. Reciprocally, forced overexpression of wild‐type PKCβII, but not an F666D mutant that cannot interact with PLD, was sufficient to enhance cell growth and increase migration of noncancerous HEK cells; indeed, both properties were almost doubled when compared to vector control and PKC‐F666D‐overexpressing cells. Notably, this condition was also dependent on both PLD and mTOR activity. In summary, these data define a PKC‐driven oncogenic signaling pathway that requires both PLD and mTOR, and suggest that inhibitors of PLD or mTOR would be beneficial in cancers where PKC overexpression is a contributing or driving factor.—El Osta, M., Liu, M. Adada, M., Senkal, C. E., Idkowiak‐Baldys, J., Obeid, L. M., Clarke, C. J., Hannun, Y. A. Sustained PKCβII activity confers oncogenic properties in a phospholipase D‐ and mTOR‐dependent manner. FASEB J. 28, 495–505 (2014). www.fasebj.org